The Paradigm Reconstruction of Indonesian Judge's Thought of Law in Adjudicating Criminal Cases - Henny Timira Handayani (The Indonesian Journal of International Clinical Legal Education, 2019)
The Indonesian Criminal Act Code (Kitab Undang-Undang Hukum Pidana/ KUHP) based on the positivistic paradigm that is directed by principle of legality, as the expression of deductive syllogisms: regulations as a major premise should be filled in by the facts which revealed as the premise minor to conclude the punishment or not. But the positivistic paradigm could not always be complied with changes in Indonesian plural society. The KUHP still applies the theory of monistic. The prove on the entire outline of the criminal element, is proving the existence unlawfulness and at the same time prove the fault/ criminal liability, unless there is a reason the criminal removal. But people demands the new criteria assessment of fairness: 1) liability not only based on fault, but also the material of justification, 2) the criminal act was not only base on formal unlawfulness, but also material unlawfulness, and 3) punishment should fit the balance of people and individual interests. That demand required the judge thought of law other than just of positivistic. This article analyzed the change of Indonesian judges‟ paradigm of thought on criminal law, the causes influenced, and the efforts that could reconstructed the fairness paradigm. This paper used double type of research technics, doctrinal research at once and empirical research, which used data collection techniques of the study of librarianship, observation and interview.